Household Food in Bandung Regency - Susniwati Susniwati; Kurhayadi Kurhayadi (Universitas Padjadjaran, 2023)
The availability of food for families living in Bandung Regency during the Covid-19 pandemic is the topic of this study's discussion. Given that the government is presently enforcing social restrictions in certain locations of Indonesia, access to affordable food is a key concern during the Covid-19 outbreak. In order to meet the family's food demands, this study will examine how access to food has changed for residents in Bandung Regency. The researcher employs a literature analysis on food availability and literacy of the effects of COVID-19 on food as an analytical tool. The approach is phenomenological, and the methodology is qualitative. According to the study's findings, the Bandung Regency Government helps households meet their food needs through direct and social access. by maintaining food security, supplying nutrient-rich food to disadvantaged individuals and groups, and evaluating trade taxes.